Does Earthworms Density Really Modify Soil's Hydrodynamic Properties In Irrigated Systems With Recycled Water? - Ababsa, N.; Kribaa, M.; Addad, D.; Tamrabet, L.; Baha, M. (University of Eloued جامعة الوادي, 2016)
Our study has the general objective to understand the impact of the valuation of treated water on earthworm abundance and total porosity of the soil and the effect of the interaction between these two physical-biological components of the hydrological functioning of soils. It was carried out on the meadows soils of the valley of Wadi Bousselam. Although the treated water has high organic and particulate filler, it improved the earthworm abundance, total porosity and hydraulic conductivity of the soil.
Articale in Journal of fundamental and Applied Sciences Vol. 08, N. 02
Keywords: meadows soils; earthworm density; soil morphology; treated water; hydrodynamic soil characteristics.